EFEKTIVITAS PERTUMBUHAN BIBIT TEBU LOKAL (Saccharum officinarum L.) DENGAN PUCUK METODE CHIP DAN RESPONSNYA TERHADAP APLIKASI PUPUK NITROGEN - Wally, Riky Geissler; Maas, Sarlota (Jurnal Pertanian Terpadu Santo Thomas Aquinas, 2022)
Sugarcane is one of the sugar-producing commodities that can improve the Indonesian economy, because it is a source of carbohydrates that are always consumed by humans for various food products. This is because the sugar cane plant produces sugar which is one of the most important basic needs for society and industry. The lack of sugarcane production in Sorong Regency is due to the lack of the number of plants being cultivated. This is because sugarcane has not been widely cultivated. Several factors that become obstacles for local communities in increasing sugarcane production include limited knowledge, lack of planted area, and low productivity. The growth of plant seeds is influenced by the sufficiency of macro nutrients N. The balance of nutrients, especially N in plants, can affect plant growth which has an impact on plant productivity. This study aims to determine the best dose of nitrogen fertilizer on the growth of sugarcane (Saccharum officinarum L.). This study used a non-factorial Randomized Block Design (RAK) design method with one factor being studied, namely nitrogen fertilization with different doses for each treatment. There were 4 treatments, with 3 replications, so the observed treatments were 12 treatments so that the number of seeds used was 36 seeds. Nitrogen fertilizer application had a significant effect on the vegetative growth of sugarcane plants, namely plant height, number of leaves, stem diameter and number of tillers. Increasing the dose of nitrogen fertilizer is closely related to the vegetative growth of sugarcane plants. Nitrogen fertilizer treatment with 0.3 gram recommended dose was significantly different on the parameters of plant height, number of leaves, stem diameter and number of tillers. However, the application of domestic waste compost at various doses was not significantly different to the length of plant roots.